Hydrogels as a new platform of therapeutic systems in oncological treatment - use as a protective barrier and drug carriers - Czerwiec, Katarzyna; Szczecińska, Weronika; Pikuła, Michał (Frontiers in Bioengineering and Biotechnology, 2025)
Hydrogels as three-dimensional polymer networks capable of reversibly absorbing water are of increasing interest among researchers. Hydrogels, especially those of natural origin such as alginate, chitosan, hyaluronic acid, peptide hydrogels, thanks to properties such as biocompatibility, biodegradability, bioactivity, can serve as an effective protective barrier or drug carrier. Thanks to the possibility of their modification, they can be an innovative platform supporting anticancer treatment. The examples presented in this publication confirm that these products can increase the effectiveness of treatment and reduce the effects of side effects.